Sharing Our Knowledge: The Tlingit and Their Coastal Neighbors - Henrikson, Steve; Kan, Sergei (UNP - Nebraska, 2015)
Sharing Our Knowledgebrings together Native elders, tradition bearers, educators, cultural activists, anthropologists, linguists, historians, and museum professionals to explore the culture, history, and language of the Tlingit people of southeast Alaska and their coastal neighbors. These interdisciplinary, collaborative essays present Tlingit culture, as well as the culture of their coastal neighbors, not as an object of study but rather as a living heritage that continues to inspire and guide the lives of communities and individuals throughout southeast Alaska and northwest British Columbia. This volume focuses on the preservation and dissemination of Tlingit language, traditional cultural knowledge, and history from an activist Tlingit perspective.Sharing Our Knowledgealso highlights a variety of collaborations between Native groups and individuals and non-Native researchers, emphasizing a long history of respectful, cooperative, and productive working relations aimed at recording and transmitting cultural knowledge for tribal use and promoting Native agency in preserving heritage. By focusing on these collaborations, the contributors demonstrate how such alliances have benefited the Tlingits and neighboring groups in preserving and protecting their heritage while advancing scholarship at the same time.